AP1-dependent galectin-1 expression delineates classical hodgkin and anaplastic large cell lymphomas from other lymphoid malignancies with shared molecular features - Rodig, Scott J. (2008)
Galectin-1 is an immunomodulatory glycan-binding protein regulated by an AP1-dependent enhancer in Hodgkin Reed-Sternberg cells. We recently found that Reed Sternberg cell Gal-1 promotes the immunosuppressive T helper2/ T-regulatory cell-skewed microenvironment in classic Hodgkin lymphoma (cHL). We sought to investigate whether the the coordinate expression of activated AP1 pathway components and Gal-1 serves as a diagnostic signature of cHL. In addition, because there are common signaling and survival pahtways in cHL and additional non-Hodgkin lymphomas, we also evaluated whether the AP1/Gal1 signature is shared by other molecularly or morphologically related lymhomas. Our findings establish a functional AP1 signature that incluses Gal-1 expression in cHL and ALCL, and suggests a common mechanmism for tumor immunotolerance in these diseases. In addition, the combination of Gal1 and c-Jun serve as diagnostic biomarkers that delineate cHL and ALCL from other lymphomas with shared morphologic and/or molecular features.